Daily Viral Kinetics and Innate and Adaptive Immune Response Assessment in COVID-19: a Case Series - Vetter, Pauline; Eberhardt, Christiane S.; Meyer, Benjamin; Martinez Murillo, Paola Andrea; Torriani, Giulia; Pigny, Fiona; Lemeille, Sylvain; Cordey, Samuel; Laubscher, Florian; Vu, Diem-Lan; Calame, Adrien; Schibler, Manuel; et al. (mSphere, 2020)
This work is particularly important because it simultaneously assessed the virology, immunology, and clinical presentation of the same subjects, whereas other studies assess these separately. We describe the detailed viral and immune profiles of the first five patients infected by SARS-CoV-2 and quarantined in Geneva, Switzerland. Viral loads peaked at the very beginning of the disease, and infectious virus was shed only during the early acute phase of disease. No infectious virus could be isolated by culture 7 days after onset of symptoms, while viral RNA was still detectable for a prolonged period. Importantly, we saw that all patients, even those with mild symptoms, mount an innate response sufficient for viral control (characterized by early activated cytokines and monocyte responses) and develop specific immunity as well as cellular and humoral SARS-CoV-2-specific adaptive responses, which already begin to decline a few months after the resolution of symptoms. Viral shedding patterns and their correlations with immune responses are still poorly characterized in mild coronavirus (CoV) disease 2019 (COVID-19). We monitored shedding of viral RNA and infectious virus and characterized the immune response kinetics of the first five patients quarantined in Geneva, Switzerland. High viral loads and infectious virus shedding were observed from the respiratory tract despite mild symptoms, with isolation of infectious virus and prolonged positivity by reverse transcriptase PCR (RT-PCR) until days 7 and 19 after symptom onset, respectively. Robust innate responses characterized by increases in activated CD14 + CD16 + monocytes and cytokine responses were observed as early as 2 days after symptom onset. Cellular and humoral severe acute respiratory syndrome (SARS)-CoV-2-specific adaptive responses were detectable in all patients. Infectious virus shedding was limited to the first week after symptom onset. A strong innate response, characterized by mobilization of activated monocytes during the first days of infection and SARS-CoV-2-specific antibodies, was detectable even in patients with mild disease. IMPORTANCE This work is particularly important because it simultaneously assessed the virology, immunology, and clinical presentation of the same subjects, whereas other studies assess these separately. We describe the detailed viral and immune profiles of the first five patients infected by SARS-CoV-2 and quarantined in Geneva, Switzerland. Viral loads peaked at the very beginning of the disease, and infectious virus was shed only during the early acute phase of disease. No infectious virus could be isolated by culture 7 days after onset of symptoms, while viral RNA was still detectable for a prolonged period. Importantly, we saw that all patients, even those with mild symptoms, mount an innate response sufficient for viral control (characterized by early activated cytokines and monocyte responses) and develop specific immunity as well as cellular and humoral SARS-CoV-2-specific adaptive responses, which already begin to decline a few months after the resolution of symptoms.